Probabilistic conversion of the compressive strength of cubes to cylinders of natural and recycled aggregate concrete specimens - Pacheco, João Nuno (2019)
This research was funded by the EcoCoRe doctoral program through the Portuguese Foundation for Science and Technology (FCT)-Fundacao para a Ciencia e a Tecnologia, grant number PD/BD/113643/2015.